Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Guru Dan Tenaga Kependidikan Di Sman 1 Haurgeulis Kabupaten Indramayu Jawa Barat - Hery Sumarno; Muhamad Ridwan; Abbas Thaha (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2023)
The purpose of this study is to analyze (1) the influence of motivation on the performance of teachers and education personnel at SMA Negeri 1 Haurgeulis Indramayu, West Java. (2) To find out the influence of work discipline on the performance of teachers and education personnel at SMA Negeri 1 Haurgeulis Indramayu, West Java. (3) To determine the influence of motivation and overall work discipline on the performance of teachers and education personnel at SMA Negeri 1 Haurgeulis Indramayu, West Java. The research hypothesis is (1) There is an influence of motivation (X1) on the performance of teachers and education personnel (Y) of SMA Negeri 1 Haurgeulis Indramayu, West Java. (2) There is an influence of work discipline (X2) on the performance of Teachers and Education Personnel (Y) of SMA Negeri 1 Haurgeulis Indramayu, West Java. (3) There is an equal influence between motivation (XI) and work discipline (X2) on the performance of Teachers and Education Personnel (Y) of SMA Negeri 1 Haurgeulis Indramayu, West Java. The research method used in this study is a survey with a correlational approach and a sample of 30 respondents was taken for data testing using validity, reliability and regression tests. The hypothesis test was carried out using a partial t test and an F test to see the effect together. The conclusion of the results of this thesis discussion is as follows: First, the results of the partial test of the influence of motivation (X1) have a significant positive influence on the performance variables of teachers and education personnel (Y). This value assumes that the higher the level of motivation of a teacher and education personnel, the better the performance of the teacher and education personnel tends to be. Second, the partial test of the influence of discipline (X2) has a significant positive influence on the performance variables of teachers and education personnel (Y). This value assumes that the higher the level of discipline of a teacher and education personnel, the better the performance of the teacher and education personnel tends to be. Third, it also has a real influence on the performance variables of Teachers and Education Personnel (Y) at SMA Negeri 1 Haurgeulis-Indramayu.